ANALISIS PENGARUH NILAI TUKAR, VOLUME PERDAGANGAN, ROA, DER, DAN SIZE TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Yang Terdaftar Pada Indeks LQ45 Periode 2011-2014) - Hedro, Nicodemus; Widyarti, Endang Tri (Diponegoro Journal of Management, 2016)
The purpose of this study was to analyze the influence of Exchange Rate, Trading Volume, Return on Assets (ROA), Debt to Equity Ratio (DER), and Size to stock price on the company that registered in the LQ45 Index between 2011-2014 on Indonesia Stock Exchange.The sampling technique used in this study is purposive sampling technique with the criteria of company that listed on LQ45 Index, and  Indonesia Stock Exchange that published annualy  financial reports periodically during 2011-2014. The data used in this study was obtained from annualy financial reports on the website of Indonesian Stock Exchange  with a sample of 22 companies. Methods of data analysis in this study using multiple regression analysis and then used assumption classic test and used hypothesis test including F-statistic test, t-statistical test and the determination of coefficients Adjusted  with a significance level of 5%.The results of the study are the independent variables simultaneously (F test) effect on stock price with a significance level of 0.000. While partially (t test) showed that  the variable Exchange Rate has negative and not significant effect on stock price. Trading Volume and DER variables has negative and significant effect on stock price. While ROA and Size has positive and significant effect on stock price. Adjusted  is 0.939 which means that the ability of the five independent variables can explain stock price amounted to 93,9%, while the rest is explained by other factors.